PEMBERDAYAAN MASYARAKAT DI DESA TANA TUKU MELALUI KEGIATAN KULIAH KERJA NYATA - Anjas Danior Andrian Djeru Logo; Febriana Bida Bara; Merliani Mamo Heo; Antonius Domu Ninggeding; Melsiani Kaita Ata Bara; Nafsia Raja; Umbu Leti Mehang Kunda; Jacky Hendrawan Pe; Rambu Kareri Emu; Yohanes Andreas Bala; Lusianus Heronimus Sinyo Kelen (Jurnal Abdi Insani, 2022)
Tana Tuku Village is located in Nggaha Ori Angu District, East Sumba Regency, East Nusa Tenggara Province with a population of 1,170 people in 2020. This village has several potentials that can be utilized and developed, as well as several problems that must be resolved. Through the thematic Real Work Lecture (from now on abbreviated as KKN), it is hoped that it will be able to reduce and provide solutions to the problems faced by the village and its community. Community Service (PkM) activities aim to empower village communities, from village officials, and groups of ikat craftsmen, to village youth and youth. The implementation of this PkM activity is carried out through thematic KKN with three stages, namely starting from the program planning stage through Project Action Planning (PAP), program implementation, and program evaluation. This KKN implementation method is carried out for one month. Thematic KKN is an annual program in KKN courses. The results can be seen from the implementation of five of the six programs in Tana Tuku Village, namely: 1) Village data and information, 2) training on natural dyes in ikat weaving, 3) socialization of delinquency and violence in courtship, 4) implementation of hamlet level sports activities, 5) Teaching 1st and 2nd-grade students related to literacy and numeracy. This program was implemented well and involved various partners, such as village officials, youth organizations, ikat groups, and village communities. Various programs carried out in the village encourage the empowerment of the village community